(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2014)
Converging media refers to integration of distinct media of creating, sharing, accessing and consuming information with shared interface. Technological convergence has steered the blending of old media, such as newspapers and radio, with the new forms of media like online communication, while offering the advantages of both. The growth in digital communications has not only facilitated the enhanced interaction among masses but it has also provided a platform for news organizations to reach a wider audience with increased swiftness. Such a platform proved to be an influencing means of aid for December 16th, 2012 Delhi gang-rape case proceedings. The exclusive inclusion of both national and foreign media in this unfortunate incident inspired a whole generation to stand together for women’s rights and more stringent laws regarding women’s safety. Converging media not only restrained itself to just tracking the case, rather it led the individuals to introspect by bringing the incident to global attention. This incident unlocked the pathway to use social media for sharing information and mustering the needed support for a given cause. The unison of people, owing to the various means of communication offered by the converging media, exerted an inevitable societal pressure which commanded accelerated hearings and trials related to the case, evidently resulting in deliverance of swift justice. The objective of the present study is to review the inducing role played by various resources of converging media in covering as well as triggering the onset of fast-tracking the prosecutions of December 16th, 2012 gang-rape case.